The effect of the formalin-fixed paraffin-embedded process on salivary microbiota profiling - SANO, Hiroto; SATO, Takuichi; KANRI, Yoriaki; ONO, Junya; OKADA, Yasuo (Biomedical Research, 2023)
In recent years, bacterial DNA in formalin-fixed paraffin-embedded (FFPE) samples has been recognized as a valuable bioresource for microbiota studies. This study aimed to examine the effect of the FFPE process on microbiota profiling to evaluate whether FFPE samples could serve as an alternative bioresource to fresh samples in oral microbiota studies. Fresh saliva was collected from nine subjects. The pellets obtained by centrifuging the collected saliva were fixed in formalin, then dehydrated and embedded in paraffin to prepare FFPE samples. The abundance of the hypervariable regions V1–9, V1–2, and V3–4 of the 16S rRNA gene in fresh and FFPE samples was relatively compared. In addition, microbiota profiling was performed to compare the results between the two sample types. The results showed that the FFPE process resulted in a certain degree of fragmentation of the 16S rRNA gene. However, the V1–2 region was relatively well-preserved compared to the V1–9 and V3–4 regions, suggesting that short regions are suitable targets for oral microbiota analysis. Importantly, there were no significant differences in alpha and beta diversity of microbiota between fresh and FFPE samples, and microbiota profiles were similar between the two sample types, suggesting that FFPE samples could be a valuable bioresource for oral microbiota studies.